(untitled) (Bangladesh Journal of Agricultural Research, 2014)
The experiment was conducted at the research field of Agronomy Division, BARI, Joydebpur, Gazipur during consecutive seasons of 2011-12 and 2012-13 to optimize fertilizer rate for potato hybrid maize relay cropping system. Seven treatments viz., T1= Farmers? fertilizer dose of potato (FFDP: N504P162K309 kg/ha) + Farmers? fertilizer dose of hybrid maize (FFDM: N0 P0 K0 kg/ha), T2= FFDP + 100% N of recommended fertilizer dose of hybrid maize (RFDM: N255 P55 K140 S40 Zn6 B2 kg/ha), T3= FFDP + 100% N & 25% others of RFDM, T4= FFDP + 100% N & 50% others of RFDM, T5= Recommended fertilizer dose of potato (RFDP: N198 P44 K194 S24 Zn6 B1.2 kg/ha) +100% N of RFDM, T6= RFDP +100% N & 25% others of RFDM, and T7= RFDP +100% N & 50% others of RFDM were tested on potato-hybrid maize relay cropping system. Potato (var. Diamant) and hybrid maize (var. BARI Hybrid Maize-9) were used in this experiment. Results indicated that yield of potato (28.38 - 28.83 t/ha) did not differ significantly but yield of hybrid maize (4.90 - 8.74 t/ha) varied significantly under different treatments. The higher grain yield (8.74 t/ha) of hybrid maize was recorded in farmers? fertilizer dose of potato or recommended fertilizer dose of potato (8.61 t/ha) along with 100% N plus 25% other fertilizers or 100% N plus 50% other fertilizers from recommended dose of hybrid maize. The highest potato equivalent yield (41.94 t/ha) and gross return (Tk. 335520/ha) were obtained from FFDP along with 100% N plus 25% others of RFDM (T3). But the highest gross margin (Tk. 219790/ha) and benefit cost ratio (3.01) were found from RFDP along with 100% N plus 25% others of RFDM (T6). The results revealed that recommended fertilizer rate of potato (N198 P44 K194 S24 Zn6 B1.2 kg/ha) along with 100% N plus 25% other fertilizers from recommended fertilizer rate of hybrid maize (N255 P55 K140 S40 Zn6 B2 kg/ha) might be optimum for potato hybrid maize relay cropping system for obtaining higher economic return. DOI: http://dx.doi.org/10.3329/bjar.v39i2.20443 Bangladesh J. Agril. Res. 39(2): 351-357, June 2014